2021
DOI: 10.2147/jir.s327538
|View full text |Cite
|
Sign up to set email alerts
|

Functional Mechanism of Bone Marrow-Derived Mesenchymal Stem Cells in the Treatment of Animal Models with Alzheimer’s Disease: Inhibition of Neuroinflammation

Abstract: The transplantation of bone marrow-derived mesenchymal stem cells (BMMSCs) alleviates neuropathology and improves cognitive deficits in animal models with Alzheimer’s disease. However, the underlying mechanisms remain to be determined. Available data demonstrate transplanted BMMSCs can inhibit neuroinflammation, which may be related to microglial M1/M2 polarization and is regulated by the secretion of autocrine and paracrine cytokines. BMMSCs also mitigate Aβ plaques and Tau tangles in the brain, which may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 119 publications
0
20
0
1
Order By: Relevance
“…Therefore, effects of cell replacement therapy on cognitive recovery have not been assessed in this study. Similarly, although cell replacement therapy has been found to decrease neuroinflammation, 22,23 this was not investigated in the current study; neuroinflammation in the VWM brain is lacking in relation to the structural white matter damage, with meager astrogliosis, 5 axonal damage secondary to astrocytic pathology, 24 and no significant microglial activation 5,6 …”
Section: Methodsmentioning
confidence: 76%
“…Therefore, effects of cell replacement therapy on cognitive recovery have not been assessed in this study. Similarly, although cell replacement therapy has been found to decrease neuroinflammation, 22,23 this was not investigated in the current study; neuroinflammation in the VWM brain is lacking in relation to the structural white matter damage, with meager astrogliosis, 5 axonal damage secondary to astrocytic pathology, 24 and no significant microglial activation 5,6 …”
Section: Methodsmentioning
confidence: 76%
“…As aforementioned, neuroinflammation plays a pivotal role in the pathogenesis of AD, and astrocytes can aggravate inflammatory conditions. Because mesenchymal stem cells can convert microglia and astrocytes from pro-inflammatory phenotypes M1 and A1 to anti-inflammatory phenotypes M2 and A2, it is believed that MSCs therapy can alleviate the neuroinflammatory response and neuronal damage in AD ( Wei et al, 2018 ; Zhao et al, 2018 ; Qin et al, 2021 ). Zhao et al (2018) recently showed that intracerebral transplantation of menstrual blood-derived MSCs dramatically improved the spatial learning and memory of APP/PS1 mice and the expression of proinflammatory cytokines was remarkably reduced.…”
Section: Mesenchymal Stromal Cells Ameliorate Astrocyte-related Neuro...mentioning
confidence: 99%
“…By boosting the expression of miR-146a and reducing the IRAK1, TRAF6, and NF-κB expression in astrocytes, EE might well be able to prevent cognitive damage [ 83 ]. Additionally, EVs enriched with miR-146a generated by bone marrow mesenchymal stem cells (BM-MSCs) in AD mice reduce astrocytic inflammation and enhance cognitive performance [ 86 ]. EVs released from BM-MSCs contain microRNA (miR)-146a, which is transferred into astroglia to reduce the inflammation brought on by diabetes [ 87 ].…”
Section: The Role Of Astrocytic Micrornas In Multiple Pathways In Admentioning
confidence: 99%